2007
DOI: 10.1227/01.neu.0000298908.94129.67
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Postoperative Patient Posture in the Recurrence of Traumatic Chronic Subdural Hematoma After Burr-Hole Surgery

Abstract: Assuming an upright posture soon after burr-hole surgery was associated with a significantly increased incidence of CSDH recurrence but not with a significant change in other position-related postsurgical complications. According to this result, it is not recommended that elderly patients assume an upright posture soon after burr-hole surgery to prevent postoperative atelectasis and dementia, as these might significantly increase the risk of CSDH recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
103
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 163 publications
(114 citation statements)
references
References 20 publications
7
103
1
3
Order By: Relevance
“…However, whether drainage alone or drainage with irrigation is better for patients with CSDH remains unclear [1,2,4,5,[10][11][12][13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…However, whether drainage alone or drainage with irrigation is better for patients with CSDH remains unclear [1,2,4,5,[10][11][12][13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…20 The study concluded that assuming an upright posture soon after burr-hole surgery is associated with an increased incidence of CSDH recurrence. Another study showed similar but statistically non-significant higher recurrence rate of CSDH with early sitting up posture in comparison to 3 days of bed rest.…”
Section: 13mentioning
confidence: 96%
“…Abouzari et al 20 conducted a study looking at the role of posture in post-operative patients in the recurrence of surgically managed traumatic CSDH. 20 The study concluded that assuming an upright posture soon after burr-hole surgery is associated with an increased incidence of CSDH recurrence.…”
Section: 13mentioning
confidence: 99%
See 2 more Smart Citations